If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3) = 3 Reorder the terms: (-3 + 2x) = 3 Remove parenthesis around (-3 + 2x) -3 + 2x = 3 Solving -3 + 2x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 3 + 3 2x = 3 + 3 Combine like terms: 3 + 3 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| -2y-10=3y+4 | | 3(x-7)=2(x+6) | | 0.6-0.1(1.41-3x)=0 | | 3(5x-2)+27=-24 | | 33+3y-4=14y-13-5y | | d=200-50d | | r^2-8r+12=0 | | 7x^2-7x=1 | | 5(y-3)=2y+9 | | n-10=13 | | 7a/2+1=18 | | 2(y+8)=7+2y | | 3106-530.3-317.4= | | -17+x/2=35 | | 16x^2-16x+5=0 | | 11-x/8=15 | | -3x+17+5x+17=2 | | 2n=5+7 | | 7x-(3x-16)=52 | | -28+p=7(p+10) | | X+70=330 | | -4=8-2x | | 23-2x=4x+5 | | 6y-7=4y+7 | | 42x-16=-7 | | (3x+12)-20=3x+36 | | 7x-3x-16=52 | | 4(5x+4)=16x | | 5.85x^4+7=16 | | 6x-3=-36 | | 8(x+3)=3x+9+7x | | -1y+6y=-6 |